2007
DOI: 10.1110/ps.072831607
|View full text |Cite
|
Sign up to set email alerts
|

Chemical cross‐linking of the chloroplast localized small heat‐shock protein, Hsp21, and the model substrate citrate synthase

Abstract: The molecular mechanism whereby the small heat-shock protein (sHsp) chaperones interact with and prevent aggregation of other proteins is not fully understood. We have characterized the sHsp-substrate protein interaction at normal and increased temperatures utilizing a model substrate protein, citrate synthase (CS), widely used in chaperone assays, and a dodecameric plant sHsp, Hsp21, by chemical cross-linking with 3,39-Dithiobis[sulfosuccinimidylpropionate] (DTSSP) and mass spectrometric peptide mapping. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 50 publications
2
55
0
1
Order By: Relevance
“…The combination of multiple N-terminal binding sites appears to form the highest affinity interaction with substrate compared with other regions of the sHSP. Previous studies have suggested there are both high and low affinity substrate binding sites on sHSPs (25,29). Our results complement this idea by demonstrating that sHSPs can bind to substrate through a plastic interaction surface.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The combination of multiple N-terminal binding sites appears to form the highest affinity interaction with substrate compared with other regions of the sHSP. Previous studies have suggested there are both high and low affinity substrate binding sites on sHSPs (25,29). Our results complement this idea by demonstrating that sHSPs can bind to substrate through a plastic interaction surface.…”
Section: Discussionmentioning
confidence: 97%
“…However, these data do not distinguish between disruption of substrate interaction sites on the N-terminal arm, versus perturbation of some other sHSP property, such as oligomer integrity, which then indirectly impacts chaperone activity. Other data suggest there are additional substrate binding sites on the ␣-crystallin domain, particularly in certain regions involved in oligomer contacts (10,14,24,25).…”
mentioning
confidence: 99%
“…Hsp21 from Arabidopsis was seen to exist as a dodecamer. Numerous substrate-binding sites and intra-oligomer interaction sites were mapped on to its N-terminal arm (Ahrman et al 2007). A structure model of Hsp21, from single-particle electron microscopy studies showed that it too existed as a doubledisc dodecamer, albeit with a relative rotation between the two discs, when compared with the wheat Hsp16.9 dodecamer (Lambert et al 2011).…”
Section: Hsp267 Chloroplastmentioning
confidence: 99%
“…Recombinantly expressed Hsp21 from Arabidopsis thaliana (UniProtKB ID P31170) was obtained as previously described (Ahrman et al 2007b). MDH (UniProtKB ID P00346) from Sus scrofa (pig) was purchased from Roche (Basel, Switzerland).…”
Section: Proteins and Reagentsmentioning
confidence: 99%